The Influence of DPK, CAR, NPF, FDR, and BOPO on the Profitability of Sharia Banks Listed on the Indonesia Stock Exchange in 2018-2022 - Mubarokah Mubarokah (Publikasi Indonesia, 2024)
In the modern era, the banking industry is one of the key sectors that make a significant contribution to the economy of a country, including Indonesia. With the enactment of Law No. 10 of 1998 on banking which was later updated into Law No. 21 of 2008 on Islamic banking, the Indonesian banking industry has received a positive response. This study aims to examine the contribution of several factors to the financial performance of banks. These factors are Third Party Deposits (DPK), Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operating Expenses Operating Income (BOPO). The descriptive statistical analysis method is used in this study, involving the incorporation of each variable with the average value, minimum value, maximum, and standard deviation. The results of the analysis show that deposits have a negative impact on profitability, CAR has a positive and significant impact on profitability, NPF has a positive and significant impact on profitability, FDR has a negative and significant impact on profitability, and BOPO has a negative and significant impact on profitability. Using Signal Theory, this study highlights the importance of management actions in conveying information to investors to reduce information inequality between management and external parties. This study has limitations such as the use of secondary data that has been published with time series data for only five years (2018-2022), and only involves five independent variables.